(3WHbGJ GdabgGAs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s ((3CHhGdWGgQ Hf CHj YHOGddg GdMSjf Hf CHj GdbGSe GdbjSQGfj GdCfUGQj s)
(3ChdgG (B:s
(3gPG cJGH eNJUQ adi PcQ GdabgGA h CfSGHge heHdZ CYeGQge s
(3BNQgG (B:s
(3hhaGJg SfI SJ hNeSjf hKdGKeGFI, hbO PcQJg ai CUMGH eGdc s
(3GfXQ Qbe (B317s
(3Qbe (B1130 (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs